METAPHORIZATION OF THE CRIMEAN WAR BY THE RUSSIAN LANGUAGE CONSCIOUSNESS - Ramazanova, Shalala; Tretyakova, Liudmila; Mokashov, Vitaliy (Revista Inclusiones, 2019)
The article describes the metaphoric model of the concept of "war" / “The Crimean War". The methods of field description, linguoculturological analysis, identifying signs used in the analysis of language material allow describing the concept of “war” / “The Crimean war” as a complex multilevel concept. The article proves that the denotation of the concept has a broad lexical objectification, since war is a significant event in the life of any nation, ethnic group.